Analysis of nano-grating-assisted light absorption enhancement in metal-semiconductor-metal photodetectors patterned using focused ion-beam lithography - Das, Narottam; Karar, A.; Vasiliev, M.; Tan, C.; Alameh, K.; Lee, Y. (2011)
We present finite-difference time-domain (FDTD) analysis results of light absorption enhancement factor dependence on the profile shape of nano-gratings etched into the surfaces of metal-semiconductor-metal photodetector (MSM-PD) structures. The MSM-PDs patterned by nano-gratings are optimized geometrically, improving the light absorption near the design wavelength through plasmon-assisted electric field concentration effects. FDTD simulation results show about 50 times light absorption enhancement prediction for 850 nm light due to improved optical signal propagation through the nano-gratings in comparison with the conventional MSM-PD designs employing only a subwavelength aperture. We also report on the nano-grating profile shapes obtained typically in our experiments using focused ion-beam lithography and discuss the dependency of light absorption enhancement on the geometric parameters of nano-gratings inscribed into MSM-PDs. © 2010 Elsevier B.V. All rights reserved.